Sustainability in the local economic development strategies of Thembisile Municipality - Mothoa, Simon (University of Limpopo (Turfloop Campus), 2007)
This study had two aims. Firstly, it investigated the existence of the Local Economic Development (LED) strategy, and secondly, the sustainability of such a strategy at the Thembisile municipality in Mpumalanga province. The rationale behind this study was to provide the municipality with possible mechanisms to improve the development and implementation of the LED policy. The concept of Local Economic Development has been studied and debated widely in South Africa. The importance of introducing policies that assist to stimulate economic activities at the local sphere of government has been acknowledged by a number of scholars. The LED policy in South Africa was developed as a way of creating a platform for municipalities to play a role in economy of the municipality and the country. This study focused on how the LED policy has been developed and implemented at the Thembisile municipality. In order to achieve this, various strategies were used to collect data. Firstly, policy documents such as the Mpumalanga Provincial Growth and Development Strategy and the Thembisile Municipality’s LED strategy were studied. Secondly, questionnaires were administered to participants. Interviews were also conducted with members of the LED Committee at the municipality and entrepreneurs. The study mainly used the Evaluation Research methods to analyze the various critical aspects of policy implementation. The results of the study show that there are possible improvements both in the development and implementation of the LED strategy at Thembisile municipality. It is also critical that the element of sustainability enterprises established should be prioritized. Finally, the study provides recommendations for improvement for the municipality.
Thesis (MPA) --(University of Limpopo), 2007
Keywords: Sustainability; Local economic development strategies; 338.968; Municipal government -- South Africa; Economic development; Sustainable development -- South Africa; South Africa -- Economic policy